2022
DOI: 10.1177/00185787221095737
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron Associated Angioedema: A Case Report

Abstract: Purpose: To review a case of angioedema associated with mirabegron. Summary: A 77-year-old woman presented to the emergency department with swelling of the left anterior side of the tongue beginning 90 minutes prior to arrival. She noticed tingling on her tongue while eating a hamburger, chips, and ice cream. The patient had no history of medication-related allergies. Home medications include acetaminophen, aspirin, biotin, black cohosh, Co-enzyme Q-10, cranberry, fish oil, multivitamin, alendronate, and mirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some other new and unexpected adverse events, including lip swelling, swollen tongue, mouth swelling, peptic ulcer, ischemic colitis, eyelid edema, glaucoma, and retinal vein occlusion, were also identified in this study. Matthew et al ( Zuchowski et al, 2022 ) reported a case of a patient who experienced tongue swelling, accompanied by difficulty breathing and swallowing, after using mirabegron. In this report, swelling was also observed in areas such as the lips, oral cavity, and eyelids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some other new and unexpected adverse events, including lip swelling, swollen tongue, mouth swelling, peptic ulcer, ischemic colitis, eyelid edema, glaucoma, and retinal vein occlusion, were also identified in this study. Matthew et al ( Zuchowski et al, 2022 ) reported a case of a patient who experienced tongue swelling, accompanied by difficulty breathing and swallowing, after using mirabegron. In this report, swelling was also observed in areas such as the lips, oral cavity, and eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, swelling was also observed in areas such as the lips, oral cavity, and eyelids. The mechanism of mirabegron-induced edema is believed to be a type I hypersensitivity reaction mediated by mast cell degranulation ( Zuchowski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations